Analisis Faktor yang Mempengaruhi Purchase Intention Produk Skincare Dengan Mediasi Trust pada Kalangan Generasi Z di Kota Batam - Marcelina Victoria; Lily Purwianti (Universitas Batanghari Jambi, 2022)
The author conducted this study with the aim to identify and analyze the factors that influence the purchase intention of skin care products through e-commerce. In this case, the author chose Generation Z in Batam City, aged 8 to 23, as the study's subject since they are familiar with local skin care goods and intend to purchase them via e-commerce.The independent variables used in this research are social influence, reputation, price value, familiarity and information quality. The intervention variable used is trust and the dependent variable used is purchase intention. This study applies an explanatory method with a quantitative approach in data collection. The technique used by the author is the purposive sampling technique. The data in this study was analyzed using smart PLS. According to the findings of this study, a company's reputation, familiarity, and credible information are all key factors in increasing a customer's trust in purchasing a product. The better the reputation and the quality of information offered through e-commerce, the higher the level of consumer trust in the company and the higher the level of consumer familiarity with the company’s product and with the e-commerce used by the company in the transactions process. This will result in the better lever of consumer’s trust in the business. If this trust is established, the customer will be more likely to make a purchase.